Exploring Attitudes of Pakistani and Canadian Children towards Television Advertisements: A Cross-cultural Comparative Analysis. (September 2014) - Langrial, Sitwat; Kashif, Muhammad; Ehsan, Usman
Children from different socio-cultural backgrounds experience and cognise television advertisements differently, which is always interesting research area to investigate. Previously advertising researchers have reported that children are valuable consumers with the ability to develop their own attitudes towards television advertisements. This article reports findings from a qualitative study that examines children's attitudes towards television advertisements in a cross-cultural context. Focus-groups were conducted in Pakistan and Canada because of distinctive cultural differences between the two countries. In all, 72 children volunteered to partake the study (N = 72) where 36 participants were recruited from Canada and the same number of Pakistani teens participated. The study compared the attitudes of Canadian and Pakistani teenagers towards television advertisements in the product category of foods and snacks. This research study is unique in presenting a cross-cultural picture of children's attitudes towards televised food advertisements. The uniqueness of study is evident in its contribution to the cross-cultural consumer socialisation phenomenon that would be beneficial for practitioners and regulatory authorities. The findings outline significant differences between the two subject groups. Importantly, the study presents theoretical and practical implications for researchers. It adds to the literature related to children's socialisation issues and attitudes towards television advertisements. Additionally, it highlights key implications for marketing agencies that strive to develop a foothold in Pakistani and Canadian food markets.